Direction set based Algorithms for adaptive least squares problems improvements and innovations. - Ahmad, Noor Atinah (Universiti Sains Malaysia, 2008)

(untitled)
The main objective of this research is to provide a mathematically tractable solutions to the adaptive filtering problem by formulating the problem as an adaptive least squares problem. This approach follows the work of Chen (1998) in his study of direction-set based CDS) adaptive filtering algorithm. Through the said formulation, we relate the DS algorithm to a class of projection method.